2018
DOI: 10.3389/fphys.2018.00540
|View full text |Cite
|
Sign up to set email alerts
|

Rat Pial Microvascular Changes During Cerebral Blood Flow Decrease and Recovery: Effects of Cyanidin Administration

Abstract: The reactive oxygen species (ROS) are known to play a major role in many pathophysiological conditions, such as ischemia and reperfusion injury. The present study was aimed to evaluate the in vivo cyanidin (anthocyanin) effects on damages induced by rat pial microvascular hypoperfusion-reperfusion injury by cerebral blood flow decrease (CBFD) and subsequent cerebral blood flow recovery (CBFR). In particular, the main purpose was to detect changes in ROS production after cyanidin administration. Rat pial microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Both models of ischemia induction (global and focal) were applied in studies on the effects of ACN administration. Some studies reported their beneficial effect when administered before stroke induction [82,180,181,182,183,184], others after the stroke induction [165,185,186], while a third set of studies monitored the effects of ACN administration before and after stroke induction [81,187,188,189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
See 2 more Smart Citations
“…Both models of ischemia induction (global and focal) were applied in studies on the effects of ACN administration. Some studies reported their beneficial effect when administered before stroke induction [82,180,181,182,183,184], others after the stroke induction [165,185,186], while a third set of studies monitored the effects of ACN administration before and after stroke induction [81,187,188,189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
“…Two studies investigated the effects of ACND pre-treatment and post-treatment on stroke induced in the same rats [81,189], indicating that neuronal damages were attenuated in the rat brains with induced stroke (by 30 min BCCAO) and that received Mv and Cy, respectively. It was also found that Cy and Mv acted against vessel wall damage in the rat brains by diminishing leukocyte adhesion and microvascular leakage as well as they reduce ROS production (by using 2′,7′-dichlorofluorescein-diacetate assay) [81,189]. An unexpected result was obtained for Cy-treated group when a greater reduction in infarct size was recorded at a lower dose [189].…”
Section: Evidence For Anthocyanins’ Effects In the Prevention And mentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that quercetin protects pial microvasculature against damage induce by hypoperfusion and reperfusion at the dosage of 5 and 10 mg/kg b.w. We used dosages of catechin and cyanidin in the same range as for quercetin and we found significant protection with all polyphenolic substances (Lapi et al, 2012a;Mastantuono et al, 2015Mastantuono et al, , 2018. The amounts of polyphenols present in the pomace extract are smaller than those previously used (Lapi et al, 2012a(Lapi et al, , 2015Mastantuono et al, 2015Mastantuono et al, , 2018; however, the protection exerted by Taurisolo was significant.…”
Section: Discussionmentioning
confidence: 83%
“…We used dosages of catechin and cyanidin in the same range as for quercetin and we found significant protection with all polyphenolic substances (Lapi et al, 2012a;Mastantuono et al, 2015Mastantuono et al, , 2018. The amounts of polyphenols present in the pomace extract are smaller than those previously used (Lapi et al, 2012a(Lapi et al, , 2015Mastantuono et al, 2015Mastantuono et al, , 2018; however, the protection exerted by Taurisolo was significant. Therefore, it is reasonable to suggest that the natural mixture of polyphenols, a component of the pomace extract, could potentiate the effects of each substance, facilitating protection of cerebral microcirculation during ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 83%